STABILITAS DIMENSI BERDASARKAN SUHU PENGERINGAN DAN JENIS KAYU - sin, Moch; H. Usman, Fadillah (Universitas Tanjungpura, 2014)
Variance in water contains and weight of wood are influenced by several factors including the drying temperature and the type of wood. This study was conducted to determine the effect of drying temperature and the type of wood on the dimensionstability. Design factorial in completely randomized design (CRD) consisting of 2 factors which are the temperature drying of wood (500C, 700C, 900C, 1100C) and the type of wood (Lagerstroemia speciosa Pers and Dracontomelon mangiferum BI). The results showed that the drying temperature and the type of wood give significant effect and highly significan on the dimensional stability of wood. All treatment drying temperature on the wood Lagerstroemia speciosa Persshowed good dimensional stability values ​​with the ratio of T / R is greater than 1, wherein the drying temperature of 1100C showed the ratio of T / R from the bottom at 1,02.After air dry, then the stability of the value dimensions is catagorized to in good category with the lowest ratio of T / R from Lagerstroemia speciosa Pers wood and Dracontomelon mangiferum BIwood arround temperature 1100C with a value of 1,11. Lagerstroemia speciosa Pers wood moisture content in the tangential area with drying temperature 1100C the lowest, value is 3,5529 %. But in general all treatment for drying temperature has shown the value of water content below 17 % which is at equilibrium moisture content between 12 % - 20%. The highest Wood density values ​​for Lagerstroemia speciosa Persis 0,6925 gr/cm3,while for Dracontomelon mangiferum BI timber the highest value is 0,7101 gr/cm3. Keywords : Dimensional stability, temperatur drying , types of wood